PENGARUH SENAM KAKI DIABETIK TERHADAP SENSITIVITAS KAKI PADA PENDERITA DIABETES MELITUS DI PUSKESMAS SUDIANG KECAMATAN BIRINGKANAYA KOTA MAKASSAR - Ningsih Jaya; Heriansyah Heriansyah; Ambo Dalle; Nasrullah Nasrullah; Nurhasanah Nurhasanah (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2020)
Diabetes Mellitus is a chronic condition that is marked by an increase in blood glucose concentration with the appearance of typical main symptoms, namely urine that taste sweet in large numbers. One of the most common complications of diabetes mellitus is the diabetic foot, which has signs and symptoms such as injury, infection and gangrene. Handling efforts in diabetes mellitus patients as well as prevention of complications is the regularity of diabetes patients perform physical activities. One of the physical activities recommended regularly is foot gymnastic movement. Gymnastics itself is expected to reduce the incidence of complications that occur in the feet of people with diabetes mellitus such as wounds. The purpose of this study to determine the effect of foot gymnastics on foot sensitivity in people with diabetes melitus at the sub-district health center sudiang biringkanaya city of Makassar. This research uses quasi experimental design with one group pretest - posttest design. The sampling technique was done by purposive sampling with 22 respondents. This study uses Wilcoxon test with significance level (<α = 0,05). From the results of statistical tests can be concluded that there is influence of foot gym on foot sensitivity in patients with diabetes mellitus with p value = 0.000.Keywords: Diabetic foot gymnastics, foot sensitivity.